2004
DOI: 10.1023/b:drug.0000036680.52016.5f
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition, G1-arrest, and apoptosis in MCF-7 human breast cancer cells by novel highly lipophilic 5-fluorouracil derivatives

Abstract: In this study we evaluate the antitumour activity, the cell cycle arrest and apoptotic properties of novel lipophilic benzene-fused seven-membered 5-fluorouracil (5-FU) analogs in comparison to 5-FU on MCF-7 human breast cancer cells. The lipophilicities of ESB-786B, ESB-252A and ESB-928A were predicted by using the CDR option of the PALLAS 2.0 program. Cytotoxic assays were evaluated in MCF-7 cells treated with the sulforhodamine B colorimetric method. Cell cycle perturbations were studied by flow cytometry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
6
31
0
Order By: Relevance
“…The T 3 -dependent cell growth inhibition was also confirmed by FACS analysis indicating a substantial reduction of cell population entering in S phase and evidencing an increase in the percentage of resting cells in G 0 /G 1 phase of the cell cycle, as already reported for Neuro-2a cells, (Lebel et al 1994, Garcia-Silva et al 2002 rat chondrocyte primary culture (Ballock et al 2000), murine embryonic carcinoma P19 cells (Nygard et al 2003), and rat oligodendrocyte precursor cells (Tokumoto et al 1999). It is widely recognized that anti-proliferative agents can induce cell cycle perturbations associated with growth arrest (Otto et al 1996, Marchal et al 2004. In this context our results indicated that T 3 not only exerts an anti-proliferative action on our cells, but is also able to alter the cell cycle distribution.…”
Section: Tablesupporting
confidence: 79%
“…The T 3 -dependent cell growth inhibition was also confirmed by FACS analysis indicating a substantial reduction of cell population entering in S phase and evidencing an increase in the percentage of resting cells in G 0 /G 1 phase of the cell cycle, as already reported for Neuro-2a cells, (Lebel et al 1994, Garcia-Silva et al 2002 rat chondrocyte primary culture (Ballock et al 2000), murine embryonic carcinoma P19 cells (Nygard et al 2003), and rat oligodendrocyte precursor cells (Tokumoto et al 1999). It is widely recognized that anti-proliferative agents can induce cell cycle perturbations associated with growth arrest (Otto et al 1996, Marchal et al 2004. In this context our results indicated that T 3 not only exerts an anti-proliferative action on our cells, but is also able to alter the cell cycle distribution.…”
Section: Tablesupporting
confidence: 79%
“…The following two consequences can be stated: (a) in contrast to 5-FU, the six-membered compounds 11-13 provoked a G0/G1-phase cell cycle arrest when the MCF-7 cells were treated during 48 h with the IC50 of the compounds, mainly at the expense of the S-phase populations. The fact that at similar doses the novel derivatives exhibit different sequences of cell cycle perturbations in comparison with 5-FU indicates that these compounds act by different pathways [12]. In the case of 12 it is worth pointing out that, moreover, there is an increase in the G2/M-phase of the cancerous cells; and (b) the apoptotic indices of the target compounds are very important, especially for 13 (58.29% for 11, 63.05% for 12, and 76.22% for 13).…”
Section: Anti-cancer Activity Of 9-(23-dihydro-14-benzoxathiin-3-ylmentioning
confidence: 99%
“…Cell cycle a Apoptosis b a Determined by flow cytometry [12]. b Apoptosis was determined using an Annexin V-based assay [12].…”
Section: Compoundmentioning
confidence: 99%
See 2 more Smart Citations